Обоснование динамики ввода энергии в газоразрядный канал при моделировании инициирования детонации искровым разрядом - Корытченко, Константин Владимирович; Болюх, Владимир Федорович; Галак, Александр Валентинович (НТУ "ХПИ", 2011)
Сделано обоснование динамики ввода энергии в газоразрядный канал применительно к задаче моделирования инициирования детонации искровым разрядом. При расчете объемной мощности учтены потери энергии на газоразрядном промежутке. Предложено ввод энергии в канал разделить на два периода. Учтены затраты энергии разряда на ионизацию

Dynamics of energy input into a gas-discharge channel is validated as applied to a task of gas detonation initiation modeling. Specification of the volumetric spark power supplied into the discharge channel is based on a developed technique for processing experimental data obtained with oscilloscopic and photographic studies of spark discharge. Computation of the volumetric power is made with allowance for energy loss in the gasdischarge gap. It is suggested to implement energy input into the discharge channel in two periods. In the first period, energy input is carried out into a fixed-radius channel. In the second period, the dynamics of energy input is accompanied with the current-conducting channel radius extension. Ionization loss of the discharge energy is taken into account
Validation of dynamics of energy input into a gas-discharge channel by modeling of spark-discharge gas detonation initiation
Keywords: ударная волна; объемная мощность; газоразрядный промежуток; ионизация; gas-discharge channel; volumetric spark power; energy input dynamics; detonation initiation modeling